Schizophrenia spectrum disorders show reduced specificity and less positive events in mental time travel - Xing-jie Chen; Lu-lu Liu; Ji-fang Cui; Ya Wang; Antao Chen; Fenghua Li; Wei-hong Wang; Han-feng Zheng; Ming-yuan Gan; Chun-qiu Li; David Shum; Raymond CK Chan (Frontiers in Psychology, 2016)
Mental time travel refers to the ability to recall past events and to imagine possible future events. Schizophrenia patients have problems in remembering specific personal experiences in the past and imagining what will happen in the future. This study aimed to examine episodic past and future thinking in schizophrenia spectrum disorders including schizophrenia patients and individuals with schizotypal personality disorder (SPD) proneness who are at risk for developing schizophrenia. Thirty-two schizophrenia patients, 30 SPD proneness individuals, and 33 healthy controls participated in the study. The Sentence Completion for Events from the Past Test (SCEPT) and the Sentence Completion for Events in the Future Test (SCEFT) were used to measure past and future thinking abilities. Results showed that schizophrenia patients showed significantly reduced specificity in recalling past and imagining future events, they generated less proportion of specific and extended events compared to healthy controls. SPD proneness individuals only generated less extended events compared to healthy controls. The reduced specificity was mainly manifested in imagining future events. Both schizophrenia patients and SPD proneness individuals generated less positive events than controls. These results suggest that mental time travel impairments in schizophrenia spectrum disorders and have implications for understanding their cognitive and emotional deficits.